Counseling Group of Rational Emotive Behavior Therapy (REBT) and Reframing Technique to Reduce Learned Helplessness (Universitas Negeri Semarang, 2019)
The purpose of this research is to examine the effectiveness of the counseling group in rational emotive behavior therapy (REBT) and reframing technique to reduce learning helplessness in students. Randomized Pre-test–Post-test Comparison Group Design was appliedto 14 students at YADIKA Senior High School Lubuklinggau. The instrument used is the scalelearned helplessness. Data analysis techniques used were a one-wayANOVA test and post hoc test. The results showed that the counseling group REBT and reframing techniques were effective in reducing learning helplessness in students. The findings of this study prove the effectiveness of group counseling services with REBT and reframing techniques in students at Lubuklinggau, Indonesia.